The influence of the implant of cryopreserved placenta tissue on morphofunctional state of recipient’s placenta - Kuzmina, Оlga; Kuzmina, Іryna (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):240